The Welfare State : A Very Short Introduction - Garland, David (Oxford, New York Oxford University Press, 2016)
This Very Short Introduction discusses the necessity of welfare states in modern capitalist societies. Situating social policy in an historical, sociological, and comparative perspective, David Garland brings a new understanding to familiar debates, policies, and institutions.
Include Index and Illustration
Keywords: Welfare state -- Comparative government -- Europe--European Union countries